2008
DOI: 10.1593/neo.08540
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Transforming Growth Factor β1 Signaling and SMAD4 Nuclear Translocation Confer Epigenetic Repression of ADAM19 in Ovarian Cancer

Abstract: Transforming growth factor-beta (TGF-beta)/SMAD signaling is a key growth regulatory pathway often dysregulated in ovarian cancer and other malignancies. Although loss of TGF-beta-mediated growth inhibition has been shown to contribute to aberrant cell behavior, the epigenetic consequence(s) of impaired TGF-beta/SMAD signaling on target genes is not well established. In this study, we show that TGF-beta1 causes growth inhibition of normal ovarian surface epithelial cells, induction of nuclear translocation SMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 55 publications
4
45
1
Order By: Relevance
“…Yet, the degree of methylation in these ovarian cancer lines has not been proportionally correlated to their susceptibility to ADC (compare Fig. 3A and B), which strongly supports the notion that multiple epigenomic events beside DNA methylation can orchestrate gene expression in a cooperative manner, in consistent with we reported previously (35).…”
Section: Discussionsupporting
confidence: 91%
“…Yet, the degree of methylation in these ovarian cancer lines has not been proportionally correlated to their susceptibility to ADC (compare Fig. 3A and B), which strongly supports the notion that multiple epigenomic events beside DNA methylation can orchestrate gene expression in a cooperative manner, in consistent with we reported previously (35).…”
Section: Discussionsupporting
confidence: 91%
“…These modifications include acetylation, methylation, and phosphorylation. Genes involved in cell cycle regulation, such as cyclinB1 (Valls et al, 2005), p21 (Richon et al, 2000), and ADAM19 (Chan et al, 2008) have been indicated to be regulated by histone modification. Overexpression of the cancer-promoting genes claudin-3 and claudin-4 in ovarian cancer is associated with loss of trimethylated histone 3 lysine 27 (H3K27me3) (Kwon et al, 2010).…”
Section: Epigenomic Mechanisms On the Development Of Ovarian Cancermentioning
confidence: 99%
“…Our previous study revealed that downregulation of TGFβ target genes are observed in a panel of ovarian cancer cell lines. 14,18 To examine if a similar phenomenon can be observed for RunX1T1, mRNA levels of RunX1T1 were examined by quantitative real time RT-PCR in the same panel of cancer cell lines (namely, HeyC2, SKOV3, MCP3, MCP2, A2780 and CP70). Lower or no expression of RunX1T1 expression was found in all ovarian cancer cell lines as compared with IOSE cells ( Fig.…”
Section: Resultsmentioning
confidence: 96%